2023
DOI: 10.2147/ndt.s401359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guideline (CANMAT 2016) Discordance of Medications for Patients with Major Depressive Disorder in China

Abstract: Objective This survey aims to explore the current medical treatment of major depressive disorder (MDD) in China and match its degree with Canadian Network for Mood and Anxiety Treatments (CANMAT). Methods A total of 3275 patients were recruited from 16 mental health centers and 16 general hospitals in China. Descriptive statistics presented the total number and percentage of drugs, as well as all kinds of treatments. Results Selective seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It is known for its various beneficial effects, including relaxing the liver and alleviating depression, as well as clearing heat and dampness. Additionally, it has properties that can reduce swelling and relieve pain[ 62 ]. Sadeghi et al [ 63 ] reported that when comparing the two treatments' effects on patients with mild and moderate depression, they discovered that Hypericum perforatum was more effective than antidepressants.…”
Section: Overview Of Tcmmentioning
confidence: 99%
“…It is known for its various beneficial effects, including relaxing the liver and alleviating depression, as well as clearing heat and dampness. Additionally, it has properties that can reduce swelling and relieve pain[ 62 ]. Sadeghi et al [ 63 ] reported that when comparing the two treatments' effects on patients with mild and moderate depression, they discovered that Hypericum perforatum was more effective than antidepressants.…”
Section: Overview Of Tcmmentioning
confidence: 99%
“…Although monoaminergic antidepressants have been under development for half of a century, there is no strong evidence of sequenced treatment alternatives for implementing pharmacological strategies (monotherapy, combination, polypharmaceutical or augmentation strategies) [ 5 ], as well as the effectiveness between any treatments at any treatment level [ 6 ]. Moreover, there is no significant difference between the different psychopharmacological classes used as augmenters in terms of symptom severity and treatment response [ 7 ].…”
Section: Introductionmentioning
confidence: 99%